2018
DOI: 10.1002/jpen.1422
|View full text |Cite
|
Sign up to set email alerts
|

Human Milk Fortification with Bovine Colostrum Is Superior to Formula‐Based Fortifiers to Prevent Gut Dysfunction, Necrotizing Enterocolitis, and Systemic Infection in Preterm Pigs

Abstract: Used as a fortifier to DHM, BC is superior to FFs to support gut function, nutrient absorption, and bacterial defense mechanisms in preterm pigs. It is important to optimize the composition of nutrient fortifiers for preterm infants fed human milk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 48 publications
2
38
0
Order By: Relevance
“…The close contact with bacteria and its toxins induces mucosal inflammation and further deteriorate gut integrity. In the current study, gut innate immunity-and hypoxia-related genes such as LBP, MYD88, IL8, and C3 were upregulated in formula-fed pigs as shown in previous studies (12,17,18,37). LBP regulates the transcription of LPS binding proteins in enterocytes, which binds and deactivates LPS during the acute phase response to endotoxin (38).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The close contact with bacteria and its toxins induces mucosal inflammation and further deteriorate gut integrity. In the current study, gut innate immunity-and hypoxia-related genes such as LBP, MYD88, IL8, and C3 were upregulated in formula-fed pigs as shown in previous studies (12,17,18,37). LBP regulates the transcription of LPS binding proteins in enterocytes, which binds and deactivates LPS during the acute phase response to endotoxin (38).…”
Section: Discussionsupporting
confidence: 83%
“…Systemically, early colostrum feeding prevented septic shock and ameliorated neuroinflammation in preterm piglets that received intraarterial Staphylococcus epidermidis (15). In the gut, piglets fed with colostrum as minimal enteral nutrition (12), full enteral nutrition (16), or supplementation to donor milk (17,19) showed improved digestive functions, integrity, antiinflammatory responses, and NEC resistance. Several clinical trials are being performed in very preterm infants to document this for its clinical application (14,27,28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies (Pillai et al, ; Sandhu, Fast, Bonnar, Baier, & Narvey, ; Schanler et al, ) have concluded that the combined use of human milk and compatible fortifier are more beneficial to infants in meeting their nutrients and intestinal tolerance needs. However, the formula or human milk‐based fortifiers may act differently in the gut function, nutrient absorption, and bacterial defense mechanisms (Sun et al, ). Therefore, optimizing the composition of nutrient fortifiers for infants fed human milk is essential.…”
Section: Discussionmentioning
confidence: 99%
“…For the STANDARD-ALPHA diet, diluted milk was fortified with a WPC with a standard α-Lac content (Arla Foods Ingredients Group P/S), resulting in a final α-Lac concentration of 6.3 g/L, corresponding to an intake of 0.96-1.1 g α-Lac per kg body weight per day in the STANDARD-ALPHA group. Compared with normal porcine milk [32], the dilute REF diet had a lower content of all macronutrients, i.e., −44% energy, −51% protein, −44% carbohydrate, and −42% fat. The nutrient contents and osmolality of all three diets are listed in Table 1.…”
Section: Diets and Nutritionmentioning
confidence: 90%